Living in Stories Through Images and Metaphors: Recognizing Unity in Diversity - Xu, Shi Jing; Stevens, Dianne E. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2006)
ABSTRACT. Who are we as teachers and what constitutes a desirable educationalexperience? Two teachers, one Chinese and the other a white Canadian, tell“a single story [of teaching], integrated by our sense of ourselves᾿ (Crites,1971, p. 303). Our storytelling is enabled by metaphors and images that serveas tools for reflecting on our actions in life and our teaching practice, and asa catalyst for understanding our teacher knowledge (Connelly & Clandinin,1988; Hunt, 1987).VIVRE DANS DES HISTOIRES PAR LE BIAIS D’IMAGES ET DES MÉTAPHORES :RECONNAÎTRE L’UNITÉ DANS LA DIVERSITÉRÉSUMÉ. Qui sommes-nous en tant qu’enseignants et qu’est-ce qu’une expérienceéducative désirable? Deux enseignantes, une chinoise et l’autre unecanadienne blanche, racontent “une simple histoire d’enseignement, intégrédans notre perception de nous même᾿ ( Crites, 1971, p.303). Notre récitd’histoire est rendue possible avec des métaphores et des images qui nousservent d’outils dans nos actions dans la vie et dans nos enseignements pratiques,et sont un catalyseur pour comprendre nos connaissances d’enseignant.( Connelly et Clandinin 1988, Hunt, 1987).